Basic Information of the Journal - Chaturbhujeshwar Janata Multiple Campus (Chaturbhujeshwar Academic Journal, 2025)
Chaturbhujeshwar Academic Journal (CAJ) is a peer-reviewed, interdisciplinary scholarly journal dedicated to publishing high-quality research articles that address contemporary and significant issues across multiple academic domains. The journal serves as a rigorous platform for the dissemination of scholarly work in areas such as Management, Education, and the Humanities, thereby contributing to ongoing academic discourse and the advancement of knowledge. The journal is published by Research Management Cell of Chaturbhujeshwar Janata Multiple Campus, situated in Harion, Sukhepokhari, Sarlahi District. Established in 2048 B.S., the campus is affiliated with Tribhuvan University and offers a range of academic programs, including undergraduate degrees Bachelor of Business Studies (BBS), Bachelor of Arts (BA), and Bachelor of Education (B.Ed.) as well as the graduate program Master of Education (M.Ed.). With a legacy of more than three decades in providing quality higher education, the campus is dedicated to producing competent and professionally skilled human resources, including managers, educators, and other development-oriented professionals. Both the journal and the institution demonstrate a strong commitment to academic excellence, research culture, and community upliftment.